Polymorphisms in CAMKK2 may predict sensory neuropathy in African HIV patients - Goullee, H.; Wadley, A.; Cherry, C.; Allcock, R.; Black, M.; Kamerman, P.; Price, Patricia (Springer, 2016)
HIV-associated sensory neuropathy (HIV-SN) is the most common neurological condition associated with HIV. HIV-SN has characteristics of an inflammatory pathology caused by the virus itself and/or by antiretroviral treatment (ART). Here, we assess the impact of single-nucleotide polymorphisms (SNPs) in a cluster of three genes that affect inflammation and neuronal repair: P2X7R, P2X4R and CAMKK2. HIV-SN status was assessed using the Brief Peripheral Neuropathy Screening tool, with SN defined by bilateral symptoms and signs. Forty-five SNPs in P2X7R, P2X4R and CAMKK2 were genotyped using TaqMan fluorescent probes, in DNA samples from 153 HIV+ black Southern African patients exposed to stavudine. Haplotypes were derived using the fastPHASE algorithm, and SNP genotypes and haplotypes associated with HIV-SN were identified. Optimal logistic regression models included demographics (age and height), with SNPs (model p < 0.0001; R2 = 0.19) or haplotypes (model p < 0.0001; R2 = 0.18, n = 137 excluding patients carrying CAMKK2 haplotypes perfectly associated with SN). Overall, CAMKK2 exhibited the strongest associations with HIV-SN, with two SNPs and six haplotypes predicting SN status in black Southern Africans. This gene warrants further study.